Unveiling the Versatility of Titanium and Iron Nanostructures: Applications Across Medicine, Environmental Remediation and Organic Reactions - Regis Correa da Silva, Daliane (Université d'Ottawa / University of Ottawa, 2024)
With the rise of material science comes the increasing demand for multiple elements for essential applications. The overexploitation of certain minerals has raised concerns about the sustainability of these practices. Materials such as noble metals have not only limited availability but also impose environmental and social risks upon extraction and processing. Thus, it becomes imperative to search for more sustainable alternatives and explore their potential uses across various fields. This dissertation will focus on iron and titanium-based nanomaterials, employing them in diverse systems and evaluating their uses in the medical, environmental, and catalysis fields. First, iron oxide will be studied through the fabrication of magnetic nanoparticles (MNPs) coated with lignin. The capping material was chosen as a sustainable and biocompatible alternative. The relatively low toxicity of iron makes these nanoparticles a great option for therapeutic materials, particularly for antibacterial uses. The four fabricated nanoparticles - Lignin@Fe (LFe), Lignin@FeAg (LFeAg), Lignin@Co (LCo) and Lignin@FeCo (LFeCo) - exhibit mild antibacterial properties in the absence of light. However, when illuminated with a near-infrared (NIR) wavelength, 810 nm, they become powerful antibacterial agents, achieving bactericidal levels with a 6-log reduction within 5 to 30 minutes of irradiation. NIR light is advantageous as it falls within the biological window, allowing deep tissue penetration during in vivo applications. Combining the photothermal effect generated upon light irradiation with the chemical production of hydroxyl radicals (•OH) via Fenton reactions resulted in even greater bactericidal activity, achieving complete eradication (≥ 6 log units) within 1-5 minutes of incubation. Ti-based materials were also studied, specifically focusing on the semiconductor TiO₂. This is a powerful photocatalyst, but its applications are limited due to its powder form. Interested in the potential environmental uses of these materials, which benefit from fixed-bed reactions and supported catalysts, we produced three fibrous TiO₂ materials. These included TiO₂ nanofibres (TiO₂NF) and two types of TiO₂ supported on glass fibres. We observed that the range of catalytic activity towards crocin bleaching varied according to the material properties, particularly surface area. Interestingly, their behaviour in flow systems differed from that in batch ones. We found that TiO₂ deposited on glass wool (TGW) not only exhibited higher catalytic activity in flow systems but also presented itself as a more viable alternative for application in various flow systems. Further interested in this new material and its potential as an alternative for fixed bed reactors, we tested it for antibacterial activity. To our surprise, the initial experiments revealed that while TGW exhibited excellent catalytic activity in the degradation of an organic dye, its bactericidal activity was limited. This unexpected discovery prompted the development of several testing conditions, which ultimately resulted in little to no improvement in bacterial inactivation. Based on these findings, we discussed the limitations of supported catalysts and explored strategies to overcome these challenged in developing optimal candidates for water remediation under realistic conditions. Finally, the two elements, Ti and Fe, were combined to form a new magnetic TiO₂ catalyst, produced via a simple one-pot method. This catalyst leverages the excellent photocatalytic properties of TiO₂ under UVA irradiation and the magnetic behaviour of iron, which also acts as an electron acceptor, reducing electron-hole recombination. This role is typically fulfilled by noble metals, which are expensive and have limited availability. The combination of these two features produces an effective catalyst for organic reactions. The model reaction chosen was the oxidative coupling of benzyl alcohol and nitrobenzene to synthesize Schiff bases. This reaction produces industrially relevant molecules, especially in the synthesis of pharmaceuticals. Our catalyst demonstrated impressive Schiff base formation rates of about 6.8 mmol/h, approximately ten times higher than those reported in the literature. Additionally, the catalyst can be magnetically removed, facilitating its removal after the reaction.
Keywords: Nanomaterials; Photocatalysis; Iron Oxide; Titanium dioxide